Advanced HVDC Transmission Solutions for Reliable and Scalable Offshore Wind Power Integration into Modern Grids - Peter Nabende; T.G. Zengeni (National Journal of Electrical Electronics and Automation Technologies, 2025)
Rapid growth in the offshore wind energy surpasses other development opportunities to decarbonization of global power grid systems but because of large scale, it creates a great technical and economic challenge to integrate into modern grids. Typical high-voltage alternating current (HVAC) transmission suffers the problem of capacitive charging, reactive power losses and small possible transmission distances in submarine cables. High-voltage direct current (HVDC) has turned out to be the most preferred option to transmit high power over distances with less loss and with enhanced stability. Nevertheless, the current HVDC applications do not provide enough scalability of HVDC modules, fail-safe operation, and universal control schemes of multi-terminal offshore systems. This paper presents the concept of new HVDC transmission systems based on modular multilevel converter (MMC) technology, the hybrid AC/DC interfaces and adaptive control methods, which make it easy to integrate offshore wind energy into the modern grid reliably, at a large scale, and cost-effectively. A complete modeling and simulation process is built using MATLAB/Simulink and PSCAD, with realistic values of submarine cable system ( 320 kV to 500 kV, 500 2000 MW capability, 200 600 km length). The efficiency, voltage regulations, dynamic stability, and fault ride-through are taken into consideration under the performance evaluation. Based on simulation outcomes, up to 35 percent efficiency transmission improvement, 25 percent decrease in fault recovery time and a significant increase in system reliability can be realized over traditional LCC- and VSC-HVDC designs. The proposed architecture accommodates partial integration of several offshore wind farms into multi-terminal DC (MTDC) networks, which makes it possible to minimise operational costs and maximise the resilience of the grid. Such results give us a technically feasible roadmap of large-scale offshore wind integration that will help the world in achieving its renewable energy objectives and smart grid innovation in the future.